EFFECTIVENESS OF COGNITIVE-BASED INTERVENTIONS FOR IMPROVING BODY IMAGE OF PATIENTS HAVING BREAST CANCER - KHAN , AJ; KHAN , M; MUMTAZ , A (Biological and Clinical Sciences Research Journal, 2024)
Breast cancer is one of the most common tumors among women. CBT is an algorithmic, time-bound method of treatment that concentrates on altering negative cognitive processes and behavioral patterns. Objectives: The main objective of the study is to find the effectiveness of cognitive-based interventions for improving the body image of patients with breast cancer. Methods: This quasi-experimental study was conducted at Khyber Teaching Hospital Peshawar from January 2023 to January 2024. Data were collected from 105 breast cancer patients, all of whom had undergone various treatments such as mastectomy, lumpectomy, or chemotherapy, which resulted in noticeable physical changes. All patients diagnosed with breast cancer and having undergone surgical or medical treatments and experiencing concerns related to body image post-treatment with no prior history of psychiatric disorders were included in the study. Results: Data were collected from 105 patients. The results show that the intervention group experienced a significant improvement in body image, with a 45.6% reduction in Body Image Scale (BIS) scores from 22.8 ± 3.5 pre-intervention to 12.4 ± 3.1 post-intervention (p = 0.001). In contrast, the control group showed only a minimal 3.6% improvement, with scores decreasing slightly from 22.5 ± 3.7 to 21.7 ± 3.4 (p = 0.152). Conclusion: It is concluded that cognitive-based interventions, particularly Cognitive Behavioral Therapy (CBT), are highly effective in improving body image and reducing anxiety and depression in breast cancer patients.